ESWL FOR RENAL AND URETERAL STONES - Ridha, Muhammad; Soebadi, Doddy M. (Indonesian Journal of Urology, 2014)
Objective: To report patient characteristics and results of Huikang HK-V extracorporeal shockwave lithotripsy (ESWL) machine for renal and ureteral stones. Material & methods: We retrospectively analyzed medical records of all patients treated with ESWL using HK-V deviceat Department ofUrology Soetomo Hospital from May2011 - February 2012. Results: There were 241 selected patients, consisted of 148 men (61.4%) and 93 women (38.6%). Mean age was 47.8 years (range 7-87). ESWL was conducted to 130 single stones and 111 multiple stones, using fluoroscopy as guidance for 166 patients, ultrasound for 31 patients (12.9%) and both for 44 patients (18.3%). Stone location was 109 in lower pole(41%), 69 in middle pole(26%), 41 in proximal ureter (16%), 28 in upper pole (11%), 14 at renal pelvis (5%), 1 at distal ureter(0.3%) and 2 staghorn stone (0.7%).There were 130 patients with stone less than 10 mm (53.9%), 102 with stone 10-20 mm (42.3%), and 9 more than 20 mm (3.7%). There were slightly more left-sided treatment was 141 patients (58.5%). Of 181 patients with hydronephrosis (75%), 104 had DJ stent inserted (43.2%). Overall, we found 158 patients (65.5%) were stone free after treatment, 49 patients (20.3%) with residual stones less than 4 mm and 34 patients (14.1%) had more than 4 mm residuals. Conclusion: ESWL is the treatment of choice for simple renal and ureteral stones less than 20 mm (opaque and non opaque).Keywords:Extracorporeal Shockwave Lithotripsy, renal stones, ureteral stones.